Corporate environment reporting disclosure on internet in China - Yu, Liu (2008)
With the growing pressure to consider environmental impact on business operations, Corporate Environmental Reporting (CER) has been rapidly emerging as one of the most important dimensions of corporate voluntary practices. The main purpose of the current study is to examine the state of CER through Internet among Chinese top 50 listed companies as well as to determine the factors, i.e. industry sectors, profitability and company size that influence companies to use such means for Internet Corporate Environmental Reporting (ICER). The data collected in this study were secondary data which were obtained from the information disclosed in the Chinese top 50 listed companies' official Web sites. This was done by first identifying companies' Web sites and then examining the contents i.e. financial information and environmental-related information of each Web site. The findings reveal that heavy polluting industry is significantly different from non-heavy polluting industry in terms of the extent of ICER. Heavy polluting industry is found to publish more environmental-related information compared to the non-heavy polluting industry. The results also show that industry sector and company size have significant impact on the extent of ICER while profitability is found to have an insignificant impact on ICER.